O Processo de Escrita na Pós-graduação: o Academicismo Como Prática de dessubjetivação - Manso, Guilherme Brambila (2021)
This Ph.d dissertation discusses the process of writing the dissertation/thesis and its desubjectivation interface in the life of the researcher in training, understanding this issue in the scope of language studies. Considering statistical data (APGUNB, 2018) and studies in the field of psychology (MACEDO; DIMENSTEIN, 2009; CRUZ, 2020; CORRÊA; SOUZA, 2016) and education (ANDRADE, 2008; PEREIRA, 2013) on the problem of writing in graduate school, it is possible to highlight that there is a demand for more debates in linguistics on the issue. It is hypothesized that the difficulties with the writing of the dissertation or thesis are of a historical, educational, political and identity nature immersed in the subject's relationship with language. For this, it is necessary to activate a theoreticalmethodological framework that understands the researcher in training in its historicity, as well as the social, historical and ideological interface that permeates its linguistic-discursive training. In order to discuss the issues raised, this investigation primarily uses the perspective of the Bakhtin Circle (2002; 2008; 2010; 2011; 2013), in dialogue with contemporary researchers (AMORIM, 2001; AUTHIER-REVUZ, 2004; GRILLO, 2008; FARACO; 2017; SOBRAL, 2009; 2019), to reflect on Bakhtinian proposals and key concepts to the writing process in graduate school, understanding it as a responsive and responsible act and practice with alterities inscribed in different chronotopes. Investigations in the area of academic literacies is considered (LEA; STREET, 1998; STREET, 2010; BARTON, 1994; BAYHAM, 1995; FISCHER, 2006; FIAD, 2015; BESSA, 2015), specifically in the proposal to identify demands and epistemologies related to the context of writing in the Brazilian postgraduate courses. The data analyzed are of two natures, being i) quantitative and national, based on objective research results with graduate students who report their impressions and experiences with the dissertation/thesis writing process; ii) qualitative and local, at the Universidade Federal do Espírito Santo with interviews with graduate students who report the experience of writing the dissertation or thesis. The evidential paradigm (GINZBURG, 1986) allied to the dialogic perspective are the methodological directions for the analyses. The discussion of data indicates that desubjectivation marks in the dissertation/thesis writing process are related to conflicts in the search for identity belonging to graduate studies, to the conceptions of language and academic subject, to the devaluation of the scientific profession and to historical, social and economic contexts that permeate the practice of writing.